Pro-Constitutional Interpretation of Statutes. A Few Remarks Related to the Dispute about Judicial Activism - Kaczmarczyk, Hubert (Review of European and Comparative Law, 2021)
The article presents an opinion in the discussion on the limits of judicial activism. The active attitude of judges in the law-making process according to the so-called concept of ‘pro-constitutional interpretation of the law’ can be observed more and more often. While we may agree with the view that the role of a judge is to pronounce a fair verdict based on the applicable law and judges may give meaning to statutory provisions supplemented with an axiology of the Constitution, the problem appears with particular sharpness when such a pro-constitutional interpretation leads to a specific application of the provisions contra legem.